Uji Aktivitas Antibiotik Komersial terhadap Salmonella typhi - Nurwahidatul Arifa; Ana Nurjanah; Siska Ferilda; Friardi Ismed (LPPM Universitas Abdurrab, 2025)
Salmonella typhi is a persistent global health problem and is mostly reported in developing countries. Commercial antibiotics used to inhibit S. typhi are chloramphenicol, ampicillin, ciprofloxacin, cefixime, and ceftriaxone. The use of these antibiotics has been prolonged, resulting in an impact on antibiotic resistance. So it is necessary to investigate the activity of commercial antibiotics to see the latest sensitivity data against Salmonella typhi bacteria. The test was conducted using the Kirby-Bauer method (disc diffusion) with sample and standard concentrations of 3 mg/ml. Ciprofloxacin had the largest inhibition diameter (42.00 ± 0.00 mm), Activity Index (AI) 1. 38 and Relative Percentage Index (RPI) 138.46% followed by cefixime (inhibition diameter 35.00 ± 0.82 mm; AI 1.15; and RPI 115.38), ampicillin (inhibition diameter 34.67 ± 0.47 mm; AI 1.14; and RPI 114.29), and ceftriaxone (inhibition diameter 32.67 ± 0.47 mm; AI 1.08; and RPI 107.69) with chloramphenicol as standard. All commercial antibiotics proved to be still sensitive to the pathogenic bacteria S. typhi.